The Effect of X-Ray and Heavy Ions Radiations on Chemotherapy Refractory Tumor Cells - Yu, Zhan; Hartel, Carola; Pignalosa, Diana; Kraft-Weyrather, Wilma; Jiang, Guo-Liang; Diaz-Carballo, David; Durante, Marco (Frontiers in Oncology, 2016)
Purpose The purpose of this study is to link both numeric and structural chromosomal aberrations to the effectiveness of radiotherapy in chemotherapy refractory tumor cells. Materials and methods Neuroblastoma (LAN-1) and 79HF6 glioblastoma cells derived from patients and their chemoresistant sublines were artificially cultured as neurospheres and irradiated by X-rays and heavy ions sources. All the cell lines were irradiated by Carbon-SIS with LET of 100 keV/μm. However, 79HF6 cells and LAN-1 cells were also irradiated by Carbon-UNILAC with LET of 168 keV/μm and Nickel ions with LET of 174 keV/μm, respectively. The effect of radiation on the survival and proliferation of cells was addressed by standard clonogenic assays. In order to analyze cell karyotype standard Giemsa staining, multicolor fluorescence in situ hybridization (mFISH) and multicolor banding (mBAND) techniques were applied. Results Relative biological effectiveness values of heavy ion beams relative to X-rays at the D10 values were found between 2.3 and 2.6 with Carbon-SIS and Nickel for LAN-1 and between 2.5 and 3.4 with Carbon-SIS and Carbon-UNILAC for 79HF6 cells. Chemorefractory LAN-1RETO cells were found more radioresistant than untreated LAN-1WT cells. 79HF6RETO glioblastoma cells were found more radiosensitive than cytostatic sensitive cells 79HF6WT. Sphere formation assay showed that LAN-1RETO cells were able to form spheres in serum-free culture, whereas 79HF6 cells could not. Most of 79HF6WT cells revealed a number of 71–90 chromosomes, whereas 79HF6RETO revealed a number of 52–83 chromosomes. The majority of LAN-1WT cells revealed a number of 40–44 chromosomes. mFISH analysis showed some stable aberrations, especially on chromosome 10 as judged by the impossibility to label this region with specific probes. This was corroborated using mBAND analysis. Conclusion Heavy ion irradiation was more effective than X-ray in both cytostatic naive cancer and chemoresistant cell lines. LAN-1RETO chemoresistant neuroblastoma cells were found to be more radioresistant than the cytostatic naive cells (LAN-1WT), whereas this effect was not found in 79HF6 cells.